EFFECT OF INFORMATION LITERACY AND TOLERANCE OF AMBIGUITY ON MANAGERIAL PERFORMANCE OF SMEs - Meutia Meutia; Tubagus Ismail; Nurul Ummi; Desiana Rahmawati (Proceedings of AICS - Social Sciences, 2019)
The managerial performance of the company needs to be improved. Expertise in accessing and evaluating information effectively performed by a manager and the ability to identify, collect, select and analyze accounting data that will assist management in making strategic decisions and for assessing organizational effectiveness. This study aims to investigate the effect of Information Literacy, Tolerance of Ambiguity, Strategic Management Accounting and Managerial Performance. Respondents in this study were fifty-two SME owners or managers in Banten province. The study data analysis used Partial Least Square (PLS) software. The study results found that Information Literacy variable had a positive effect on Strategic Management Accounting, Tolerance of Ambiguity had a positive effect on Managerial Performance, Strategic Management Accounting had a positive effect on Managerial Performance, Information Literacy variable had a positive effect on Managerial Performance.